The relationship between total and culturable bacteria in cold soils - Stres, Blaž (Acta agriculturae Slovenica, 2007)
Cold ecosystems are essential to global ecology. Microbial activities are predicted to increase in low temperature regions due to global warming thus further affecting the green gas emissions and stored carbon overturn. This all has led to increased awareness how minute is our understanding of bacterial assemblages in the cold soils and also other environments, spurring the idea of standardization of research protocols. This work focused on comparison of recently published data on culturability of bacteria from 23 cold soils in the frame of International polar Year 2007 (IPY 2007). The results show that linear relationship exists between direct counts and numbers of cultured bacteria. 11 environmental parameters were reported in these studies. However, only two categories were present in all, preventing attempt to identify governing environmental factors. As there is such heterogeneity in reporting and performing research in microbial ecology, standardization of approaches and protocols in microbial ecology could improve comparability of results substantially.
Keywords: bakterije; gojitvene tehnike; hladna tla; mikrobiologija